PELAKSANAAN PADA MASYARAKAT MUSLIM DI KECAMATAN MUNTILAN HUKUM KEWARISAN ISLAM - , IKA KARTIKA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Three types of inheritance law applies in Indonesia, there are Burgerlijk Wetboek inheritance law, customary inheritance law and Islamic inheritance law. Each of them having own characteristic and differences. The purpose of the research in Muntilan district is to determine the implementation of Islamic inheritance law in an environment with heterogeneous people. There are indigenous Javanese muslim in the Islamic boarding school environment, in the village and town who lives side by side with people of Chinese descent. Examining the influence (or mixing) is there of other inheritance laws in the implementation of Islamic inheritance law. The study was conducted with a normative approach to empirical, and the report is descriptive analytical study. It begins with a literature study to develop a guiding frame work of research and frames. Continued field research using data collection tool, with questionnaire and a list of interview. Empirical data obtained from the public then analyzed with qualitative data analysis technique. The result of this study is: (1) The implementation of inheritance law in the muslim community at the Muntilan district not fully in accordance with Islamic inheritance law and there is no significant differences in the implementation of the Islamic inheritance law in society in the three villages which became the study sample. (2) There are two classifications of the things that affect the implementation of the Islamic inheritance law